The scholar denied : W.E.B. Du Bois and the birth of modern sociology - Morris, Aldon D. (A Naomi Schneider Book, 2015)
"In this groundbreaking book, Aldon D. Morris's ambition is truly monumental: to help rewrite the history of sociology and to acknowledge the primacy of W.E.B. Du Bois's work in the founding of the discipline. Taking on the prevailing narrative of how sociology developed, Morris, a major scholar of African American social movements, probes the way in which the history of the discipline has been written, giving credit to Robert E. Park at the University of Chicago, who worked with the conservative black leader Booker T. Washington to render Du Bois invisible. Uncovering the seminal theoretical work of Du Bois in developing a "scientific" sociology through a variety of methodologies, Morris examines how the leading scholars of the day disparaged and ignored Du Bois's work. The Scholar Denied is based on extensive, rigorous primary source research; the book is the result of a decade of research, writing, and revision. In uncovering the economic and political factors that marginalized the contributions of Du Bois, enabling Park to be recognized as the "father" of the discipline, Morris delivers a wholly new narrative of American intellectual and social history that places one of America's key intellectuals, W.E.B. Du Bois, at its center. The Scholar Denied is a must-read for everyone interested in American history, racial inequality, and the academy. In challenging our understanding of the past, the book promises to engender debate and discussion"--Provided by publisher